Reshaping chromatin after DNA damage: the choreography of histone proteins - Polo, Sophie E. (J Mol Biol, 2014)
DNA damage signaling and repair machineries operate in a nuclear environment, where DNA is wrapped around histone proteins and packaged into chromatin. Understanding how chromatin structure is restored together with the DNA sequence during DNA damage repair has been a topic of intense research. Indeed, chromatin integrity is central to cell functions and identity. Yet, chromatin shows remarkable plasticity in response to DNA damage. This review presents our current knowledge of chromatin dynamics in the mammalian cell nucleus in response to DNA-double strand breaks and UV lesions. I provide an overview of the key players involved in regulating histone dynamics in damaged chromatin regions, focusing on histone chaperones and their concerted action with histone modifiers, chromatin remodelers and repair factors. I also discuss how these dynamics contribute to reshaping chromatin and, by altering the chromatin landscape, may affect the maintenance of epigenetic information.